2017
DOI: 10.1002/path.4891
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein and Notch signalling crosstalk in poor‐prognosis, mesenchymal‐subtype colorectal cancer

Abstract: The functional role of bone morphogenetic protein (BMP) signalling in colorectal cancer (CRC) is poorly defined, with contradictory results in cancer cell line models reflecting the inherent difficulties of assessing a signalling pathway that is context‐dependent and subject to genetic constraints. By assessing the transcriptional response of a diploid human colonic epithelial cell line to BMP ligand stimulation, we generated a prognostic BMP signalling signature, which was applied to multiple CRC datasets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
(55 reference statements)
1
37
1
Order By: Relevance
“…Interestingly, BMP signaling could modulate other signaling cascades, as recently demonstrated for Notch signaling, which becomes activated by BMP-induced Smad1/5 binding to the promoter of the Notch target gene HES1 in colorectal cancer cells (Irshad et al, 2017). Such BMP-Notch signaling crosstalk, being independent of Id1, could contribute to our observed phenotypes as Notch signaling is a crucial regulator of satellite cell function (Fukada et al, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, BMP signaling could modulate other signaling cascades, as recently demonstrated for Notch signaling, which becomes activated by BMP-induced Smad1/5 binding to the promoter of the Notch target gene HES1 in colorectal cancer cells (Irshad et al, 2017). Such BMP-Notch signaling crosstalk, being independent of Id1, could contribute to our observed phenotypes as Notch signaling is a crucial regulator of satellite cell function (Fukada et al, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…[20][21][22] In contrast, GREM1, as an antagonist of BMPs, preferentially shifted the differentiation state of F I G U R E 5 Silencing GREM1 inhibited CRC-induced capillary structure formation and viability of HUVECs. [20][21][22] In contrast, GREM1, as an antagonist of BMPs, preferentially shifted the differentiation state of F I G U R E 5 Silencing GREM1 inhibited CRC-induced capillary structure formation and viability of HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that BMP4, a member of the transforming growth factor-β (TGF-β) superfamily, plays a significant role during embryonic development that regulates cell apoptosis, proliferation and differentiation [26]. Regarding the function of BMP4 in cancers, BMP4 has been indicated to mediate the differentiation of cancer stem cells and inhibit the cancer growth of CRC [94].…”
Section: Bone Morphogenetic Protein (Bmp)/smad Pathways As Important mentioning
confidence: 99%
“…The function and interaction of molecular pathways have a significant role in multiple cancer types. Previous studies have indicated that CRC progression is mediated by the dysregulation of many signaling pathways, including Wnt [19], PI3K/Akt [20,21], Hedgehog [22], ErbB [23], RHOA [24], Notch [25], BMP [26], Hippo [27], AMPK [28], NF-κB [29], MAPK [3] and JNK [30]. Moreover, the interaction of these pathways is precise and complicated.…”
Section: Introductionmentioning
confidence: 99%